2010
DOI: 10.4103/0019-5049.68370
|View full text |Cite
|
Sign up to set email alerts
|

Effects of retractor application on cuff pressure and vocal cord function in patients undergoing anterior cervical discectomy and fusion

Abstract: Anterior cervical discectomy and fusion is a commonly performed procedure for prolapse of cervical intervertebral disc. It involves retraction of soft tissue of neck for adequate exposure of anterior spinal canal. Increased cuff pressure with retractor application may affect the postoperative vocal cord function. Cuff pressures of tracheal tube were measured continuously in 37 patients using air-filled pressure transducer connected to the pilot balloon. Changes of pressure from baseline values were noted after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…This retractor is placed between the carotic sheath laterally, and the trachea and esophagus medially. Previous studies showed that after positioning and opening the retractor, the endotracheal tube (ETT) cuff pressure increases significantly [ 1 , 2 ]. Structures trapped between the retractor and the endotracheal tube cuff, like the recurrent laryngeal nerve, may be compromised.…”
Section: Introductionmentioning
confidence: 99%
“…This retractor is placed between the carotic sheath laterally, and the trachea and esophagus medially. Previous studies showed that after positioning and opening the retractor, the endotracheal tube (ETT) cuff pressure increases significantly [ 1 , 2 ]. Structures trapped between the retractor and the endotracheal tube cuff, like the recurrent laryngeal nerve, may be compromised.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true for multilevel ACDF surgery. [13][14][15][16][17] To address the concerns associated with anterior plating, stand-alone interbody cage devices have been developed including low-profile or zero-profile constructs with integrated screws. This design has been shown to provide a similar degree of biomechanical stability conferred by anterior plating, while avoiding increased retraction and anterior bulk associated with plating.…”
mentioning
confidence: 99%
“…Furthermore, plate fixation requires additional manipulation and retraction of the tissue of the anterior neck and creates additional anterior “bulk,” thereby potentially increasing the risk of transient or long-term dysphagia, or dysphonia. This is particularly true for multilevel ACDF surgery 13–17…”
mentioning
confidence: 99%
“…Significant increase in cuff pressure (168% of baseline values) and airway pressure of tracheal tube during cervical retraction in anterior cervical discectomy was observed by Garg et al . [ 7 ]…”
Section: Discussionmentioning
confidence: 99%